Pembangunan Berkelanjutan Berbasis Moral: Pemikiran Pembangunan P.A.A. Soeria Atmadja dalam "Di Tioeng Memeh Hoedjan" - Awaludin Nugraha (Jurnal Sejarah Citra Lekha, 2018)
The development is essentially a constructive effort to make a better life for everyone. Various development theories have been produced to make this happen. In the history of Indonesia, there was a Regent who inherited the developmental thoughts in the next generation. He was Prince Aria Soeria Atmadja or Prince of Mecca, Regent of Sumedang in the period of 1883-1919. He wrote his development ideas in the book “Di Tioeng Memeh Hoedjan”. The purpose of this article is to understand the developmental thoughts of Aria Soeria Atmadja. This research used the qualitative method with more emphasize on the hermeneutic approach, especially using hermeneutical circles. The result shows that the developmental thoughts of Aria Soeria Atmadja expressed in Sundanese with figurative language style because of the colonization. His thoughts were a formulation of his experience when he was in a government bureaucratic official. His developmental thoughts were in line with the Sustainable Development theory that developed in the 1980s and emphasized morality as its basis. He also emphasized the importance of community involvement in the development process